2018
DOI: 10.1002/mus.26140
|View full text |Cite
|
Sign up to set email alerts
|

Label‐free identification of myopathological features with coherent anti‐Stokes Raman scattering

Abstract: CARS enables the label-free identification of distinct myopathological features, possibly paving the way for subsequent proteomic, metabolic, and genomic analyses. Muscle Nerve 58: 457-460, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The laser power at the sample was 28 mW (Pump) and 21 mW (Stokes). Integration times of 34 s per image with a pixel dwell time of 32 µs, 1024 × 1024 pixels and a spatial resolution of 300 nm were used [54]. After the label-free detection of the lipid and protein distribution, immunofluorescent stainings were performed on the same sections (Online Resource Fig.…”
Section: Coherent Anti-stokes Raman Scatteringmentioning
confidence: 99%
“…The laser power at the sample was 28 mW (Pump) and 21 mW (Stokes). Integration times of 34 s per image with a pixel dwell time of 32 µs, 1024 × 1024 pixels and a spatial resolution of 300 nm were used [54]. After the label-free detection of the lipid and protein distribution, immunofluorescent stainings were performed on the same sections (Online Resource Fig.…”
Section: Coherent Anti-stokes Raman Scatteringmentioning
confidence: 99%
“…Recently, Karuna et al reported label-free three-dimensional quantitative imaging of chemical composition of the human osteosarcoma cell division by using the hyperspectral CARS microscopy 186 . Niedieker et al applied CARS imaging to characterize the myopathological features in muscles from patients with different myopathies, and to identify the distinct specific disease features 187 . Hirose et al developed a CARS rigid endoscope using two individual optical fibers to image rat sciatic nerves and also rabbit prostatic fascia without sample slicing, which revealed the potential application of the CARS endoscope to robot-assisted surgery 188 .…”
Section: Coherent Anti-stokes Raman Scattering Microscopic Imagingmentioning
confidence: 99%
“…Surface‐enhanced Raman significantly boosts the signal but would require injection of nanoparticles into the tissue of interest 54 . Coherent anti‐Stokes Raman spectroscopy uses two beams of light to excite the sample and has been shown to effectively map out protein distributions in human muscle biopsy samples from a range of diseases 55 …”
Section: Discussionmentioning
confidence: 99%